Ebbinghaus Illusions with Disc Figures: Effects of Contextual Size, Separation, and Lightness. Issue 3 (June 2014) - Jaeger, Ted; Klahs, Kyle; Newton, David
The Ebbinghaus illusion was produced using figures with four small or large contextual discs located either near or far from the central disc. For similar figures, the discs were either all black or all white; for dissimilar figures, black and white contextual and central discs were used in opposition. 48 observers, in equal numbers, were assigned to one of the four crossings of size and separation of the contextual discs and, using the converging method of limits, illusion magnitude scores for each Ebbinghaus configuration were obtained. The central disc appeared larger when bounded by small contextual discs and smaller when the contextual discs were more distant. Contrary to size contrast theory, uniformly colored discs did not generate greater illusions; instead, white central discs appeared larger than black ones regardless of contextual color. Collectively, the results indicated that contour interactions play a prominent role in producing the Ebbinghaus illusion.